2020
DOI: 10.1016/j.celrep.2020.108268
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprint and Developmental Regulation of the Tegmental GABAergic and Glutamatergic Neurons Derived from the Anterior Hindbrain

Abstract: Highlights d GABAergic and glutamatergic precursors contribute to tegmental nuclei d The TF Tal1 and Notch signaling control neuron differentiation in the embryonic brainstem d TFs downstream of Tal1 mark and regulate development of specific tegmental nuclei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…3A; data not shown). Similar to the Zfpm2 CKO embryos (Morello et al, 2020), the early production of rV2-derived GABAergic precursors was unaffected in Zfpm1 CKO mutants at E12.5 (data not shown). In contrast to the Zfpm2 CKO and Zfpm1 CKO ;Zfpm2 CKO mice, the pSNpr, RMTg, and VTg GABAergic neurons were present in the correct location and expressed their specific markers in Zfpm1 CKO mutants at E18.5 (Fig.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…3A; data not shown). Similar to the Zfpm2 CKO embryos (Morello et al, 2020), the early production of rV2-derived GABAergic precursors was unaffected in Zfpm1 CKO mutants at E12.5 (data not shown). In contrast to the Zfpm2 CKO and Zfpm1 CKO ;Zfpm2 CKO mice, the pSNpr, RMTg, and VTg GABAergic neurons were present in the correct location and expressed their specific markers in Zfpm1 CKO mutants at E18.5 (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Zfpm1 is not required for the development of the r1-derived posterior substantia nigra pars reticulata, rostromedial tegmental nucleus, and ventral tegmental nucleus of Gudden GABAergic neurons In addition to the serotonergic precursors, Zfpm1 was expressed by the GABAergic precursors in the rV2 domain. These precursors contribute to multiple GABAergic nuclei in the ventral midbrain and anterior hindbrain, including the posterior substantia nigra pars reticulata (pSNpr), rostromedial tegmental nucleus (RMTg) and the ventral tegmental nucleus of Gudden (VTg; Achim et al, 2012;Lahti et al, 2016;Morello et al, 2020). In addition to Zfpm1, the GABAergic precursors in the rV2 also express ZFPM2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a hindbrain-specific Cre-driver ( Gbx2 CreERT 2 ) labeled the posterior part of the SNpr (pSNpr), but not its anterior part (aSNpr). Studies of the development of GABAergic neuron subtypes in the rhombomere 1 (r1) of the anterior hindbrain have further refined the origin of the pSNpr neurons in the ventrolateral r1 neuroepithelium expressing the homeodomain transcription factor (TF) NKX6-1, and in particular the anterior part of this neuroepithelial region close to the midbrain-hindbrain border ( Morello et al, 2020a ; Figure 2A ). On the other hand, fate mapping with the Nkx6-2 CreERT 2 –driver suggested that the aSNpr neurons are derived from the Nkx6-2 expressing neuronal progenitors or precursors found in the ventrolateral midbrain-diencephalon region ( Qiu et al, 1998 ; Moreno-Bravo et al, 2010 ; Madrigal et al, 2016 ).…”
Section: The Substantia Nigra Pars Reticulata Neurons and Their Devel...mentioning
confidence: 99%
“…1B). From those, Gata3 , Tal1 , Tal2 , Zfpm1 and Zfpm2 have earlier been associated with the function of Gata2 or other Gata factors in different developmental contexts (Chlon and Crispino, 2012; Lahti et al, 2016; Morello et al, 2020; Tikker et al, 2020). ISH analysis showed that these putative Gata2 cofactors were broadly expressed in the E12.5 midbrain GABAergic neuron precursors (Fig.…”
Section: Resultsmentioning
confidence: 92%